UPAYA MENINGKATKAN HASIL BELAJAR IPS MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH DI KELAS V SDN 163094 KOTA TEBING TINGGI - Elisa Lubis (Universitas Negeri Medan, 2019)
The purpose of this study was to describe the process of implementing the Make a Match type of cooperative learning model that can improve student learning outcomes in social science subjects in the time division in Indonesia. This study uses the Make a Match type cooperative learning model as an effort to improve student learning outcomes and make students more active in the learning process. The population of this study was all students of class V, amounting to 36 people with an age range of 11-12 years. The tool used to collect data in this study is test and observation, the results of the study at the pretest obtained in the pre-cycle activities the percentage of classical completeness of students is 59.52%, then in the first cycle to 75.13%. An increase of 15.61% in the first cycle when compared to the pre-cycle activities. After the second cycle was implemented using the Make a Match cooperative learning model in the second cycle, the achievement of students' classical completeness reached 77.11%. The indicator of success in this study is the percentage of classical completeness of students of 75% of the total number of students. Keywords: IPS Learning Outcomes, Make a Match